2016
DOI: 10.17482/uujfe.77635
|View full text |Cite
|
Sign up to set email alerts
|

The Demolition of a Reinforced Concrete Building by Using Explosives and Examination of It’s Efficiency

Abstract: Ülkemizde kentsel dönüşüm kapsamında yıkılacak birçok eski veya hasar görmüş yapı olması, yeni yıkım tekniklerinin arayışına girilmesine sebep olmuştur. Yurt dışında yıllardır başarılı bir şekilde uygulanan patlayıcı ile kontrollü yapı yıkımı, avantajları düşünüldüğünde dikkate değer bir tekniktir. Bu çalışmada, Edirne Kapıkule Gümrük Lojman Binası'nın patlayıcı kullanılarak kontrollü yıkımı gerçekleştirilmiştir. Bu amaç doğrultusunda, hali hazırda bulunmayan bina planı şerit metre kullanılarak çıkarılmış ve b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Özyurt, (2013) and Özyurt et al, (2016) performed studies to determine the controlled demolition of Edirne Kapıkule Customs Building by using explosives. From the comparison of the demolition by using machines and explosives in terms of the cost, it was concluded that machine based demolition is more advantageous due to the less number of floors 8,9 . These recent progressive collapse studies were particularly those considering uncertainties and probabilistic approaches 10–12 .…”
Section: Introductionmentioning
confidence: 99%
“…Özyurt, (2013) and Özyurt et al, (2016) performed studies to determine the controlled demolition of Edirne Kapıkule Customs Building by using explosives. From the comparison of the demolition by using machines and explosives in terms of the cost, it was concluded that machine based demolition is more advantageous due to the less number of floors 8,9 . These recent progressive collapse studies were particularly those considering uncertainties and probabilistic approaches 10–12 .…”
Section: Introductionmentioning
confidence: 99%